Konsep Sabar Dalam Tafsir Al-Marâgȋ - Kurnia, Yunita Wahyu (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2016)
This article explains about patien in the perspective Tafsîr al-Marâgî. The researcher focuse on patient verses in Tafsîr al-Marâgî. Therefore, it is divided into problem statements. This ﬁ rst problem statement is: How is observation the meaning of patient? And the Second is: How is exclamation thematic exegesis the meaning of patient in Tafsîr al-Marâgî. The reason of researcher using Tafsîr al-Marâgî in this research because it is interpretation verses of qur’anic using simple language which easier understand by pople. Therefore it is used thematic exegesis methodology (mauḍû’î). The collecting data using two process are reading and interpretation relevant books and problem that inspected. Then the result of analysis is patient in Tafsîr al-Marâgî having some meaning can be implementation in the daily activity. Patient is attitude needent in life. Who is patient, Allah will reward with proportionate kindness.